Hepatoprotective effect of SRC50, a novel plant extract, against alcohol-induced liver damage by regulating antioxidant genes in NIAAA mouse model - Shin, Yang-Ji; Nho, Chu Won (KSBMB International Conference 2024: Abstract Book, 2024)
Alcoholic liver disease (ALD) is one of the most prevalent chronic liver diseases worldwide. Accumulating evidence has revealed that its progression is strongly linked to oxidative stress. We aimed to investigate SRC50, a novel plant extract, as an antioxidant for alcoholic liver disease. In this study, we used an acute-on-chronic (NIAAA) mouse model to induce alcoholic liver injury, and the hepatoprotective effect of SRC50 was evaluated in a NIAAA mouse model. Administration of SRC50 significantly decreased not only serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels but blood alcohol and acetaldehyde levels. In addition, gene expressions of nuclear factor erythroid-2-related factor 2 (Nrf2) gene, master regulator of antioxidation, and its downstream antioxidant genes including heme oxygenase-1 (Hmox-1), NADPH quinone oxidoreductase 1 (Nqo1) were elevated in the liver of the SRC50- treated group compared with the alcohol only-treated group. These results demonstrate that SRC50 is potentially to have hepatoprotective effect against alcohol induced cytotoxicity by regulating antioxidant genes.